Study on mechanism of end face roof leaks based on stope roof structure movement under repeated mining. (May 2022) - Li, Qiang; Wu, Guiyi; Kong, Dezhong; Han, Sen; Ma, Zhenqian
Highlights: The influence of stope roof structure movement on direct roof is expounded. The mechanism of roof fall under repeated mining was studied. Different instability conditions of cantilever beam structure are obtained. Reasonable support working resistance is an important reason to maintain the stability of cantilever beam structure. Abstract: In view of the problem that the broken stope roof under repeated mining is prone to end face roof leaks, this paper's research background is the close distance coal seams mining of a mine in Guizhou province, China. The impact of stope roof structure movement on the immediate roof was elucidated from the analysis of stope roof structure movement under repeated mining employing a combination method of field measurement, physical simulation, theoretical analysis, and numerical simulation. As a result, the mechanism of end face roof leaks under repeated mining is investigated, and the corresponding control measures are proposed. The results show that the cantilever beam structure instability of the stope roof under repeated mining is an important reason for the end face roof leaks and support crushing accident. The fracture forms of cantilever beam structure are divided into direct fracture and hinged structure fracture. The direct fracture is affected by the support working resistance. The cantilever beam hinged structure is divided into sliding and rotational instability. The periodic weighting interval is small and the fracture degree is large under repeated mining, which leads to the sliding instability. It is concluded that reasonable support working resistance is the important reason to keep the cantilever beam structure stability. Therefore, the stope roof leakage control countermeasures under repeated mining are proposed. The UDEC numerical simulation is used to verify the above analysis again, so as to provide the basis for the end face roof leaks prevention and control under repeated mining.